Serological and cellular response to mRNA-SARS-CoV2 vaccine in patients with hematological lymphoid malignancies: Results of the study “Cervax” - Mohamed, Sara; Lucchini, Elisa; Sirianni, Francesca; Porrazzo, Marika; Ballotta, Laura; Ballerini, Mario; De Sabbata, Giovanni Maria; De Bellis, Eleonora; Cappuccio, Ilaria; Granzotto, Marilena; Toffoletto, Barbara; Fortunati, Ilaria; et al. (Frontiers in Oncology, 2023)
mRNA-SARS-CoV2 vaccines such as BNT162b2 became available in late 2020 but hematological malignancies patients (HM pts) were not evaluated in initial registration trials. We report hereby the results of a prospective, unicentric, observational study (CERVAX) developed to assess the post-vaccine serological, and T-Cell-mediated response in a cohort of SARS-CoV2-negative HM pts vaccinated with BNT162b2. Patients with lymphomas (NHL, HL), chronic lymphocytic leukemia (CLL) and multiple myeloma (MM), off-therapy for at least 3 months, in watch-and-wait program or, in treatment with ibrutinib, venetoclax, lenalidomide were included. Different time points were considered to assess the serological response to vaccine: before the second dose (T1), at 3-6-12 months after first dose (T2-3-4, respectively). Since March 2021, 39 pts have been enrolled: 15 (38%) NHL, 12 (31%) CLL and 12 (31%) MM. Thirteen of the 39 pts (33%) seroconverted at T1; an increase of serological response was registered after the second dose (T2) (22/39 pts, 56%) and maintained after 6 months (22/39 pts, 56%) and 12 months (24/39 pts, 61%) from the first dose (T3-T4 respectively). Non-serological-responders at T4 were 7/39 (18%): 0/15 NHL/HL, 1/12 MM (8%), 6/12 CLL (50%). All of them were on therapy (1 lenalidomide, 3 ibrutinib, 3 venetoclax). SARS-CoV2-reactive T cells analysis (IGRAs) was available since June 2022 and was evaluated at 12 months (T4) from the first dose of vaccine in 31/39 pts (79%). T-Cell-mediated-responders were 17/31 (55%): most of them were NHL/HL and MM (47%, 41% and 12% for NHL/HL, MM, CLL respectively). Both serological and T-cell-non-responders were represented by pts on active therapy (venetoclax/ibrutinib). During the period of observation 8 (20,5%) pts developed mild SARS-CoV2 infection; no COVID19-related deaths or hospitalizations were registered. In conclusion, in our cohort of lymphoproliferative pts receiving BNT162b2, CLL diagnosis and venetoclax/ibrutinib seem to be related with a lower humoral or T mediated response. Nevertheless, the efficacy of mRNA vaccine in HM pts and the importance to continue the vaccine program even in non-responders after the first dose, is supported in our study by demonstrating that a humoral and T-cell mediated seroconversion should be observed even in subsets of heavily immunocompromised pts.